Ordinary People as Mass Murderers
XVIII, 228 p.
Keywords: Since the 1990s scholars have focused heavily on the perpetrators of the Holocaust, and have presented a complex and diverse picture of perpetrators. This book provides a unique overview of the current state of research on perpetrators. The overall focus is on the key question that it still disputed: How do ordinary people become mass murderers?